The Effect of Pempek Palembang Culinary Lacing Card Activities on Fine Motor Skills of Children Aged 5-6 Years - Indri Yanti; Dwi Suryani, Yuni (Yayasan Corolla Education Centre, 2025)
This study aims to determine the effect of Palembang culinary pempek lacing card activities on the fine motor skills of children aged 5-6 years at the Ogan Ilir Pilot State Kindergarten. The research method used in this research is a quantitative experimental method with a one-shot case study design. The sampling technique used was saturated sampling. This research was conducted on children aged 5-6 years at the Ogan Ilir Pilot State Kindergarten with a sample size of 16 children. The results of data analysis showed that the t count value was (5.70) and the ttable result was (1.75). Thus, t count > t table, it can be concluded that ????count ˃ ????table (5.70 > 1.75) so that ????0 is rejected, ???????? is accepted. Thus, it can be concluded that there is an influence of the Palembang culinary pempek lacing card activity on the fine motor skills of children aged 5-6 years at the Ogan Ilir Pilot State Kindergarten.